Edukasi Bahaya Narkoba, Kenakalan Remaja Dan Kesadaran Berlalu Lintas Pada Masyarakat Di Desa Sangketan - Komang Sri Widiantari; I Wayan Ferdy Pratama (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
Juvenile delinquency and violating traffic ethics are deviant behaviors that are often found in adolescents in Sangketan Village, this behavior is often seen when smoking and drinking alcohol, speeding on the streets and things that are against the law, religious teachings and social norms can disturb the environment. From these problems, counseling was carried out about Juvenile Delinquency, Drugs and Traffic Awareness. The method used is Participatory Rural Appraisal (PRA). All service activities are designed to solve partner problems with three main stages namely (1) planning, (2) implementation, (3) evaluation. The result of this activity is that people understand more about the dangers of sexual violence, juvenile delinquency and drugs.